Informasi Genetik Bitti (Vitex cofassus) di Areal Sumber Daya Genetik (ASDG) BPTH Wilayah II Sulawesi - Siti Halimah Larekeng; Zulfadilah Syam; M Musriati; Rathna Paelongan; Astuti Arif; Muhammad Restu; I Iswanto (Fapetrik-UMPAR, 2021)
Bitti (Vitex cofassus) is one of the most important tree species in Sulawesi, which is used as material for phinisi boats. The aim study was to study the genetic diversity of Bitti in the genetic resources area in Bone Regency. This study used provenance Bulukumba, Muna, Kolaka, and North Luwu proof which was analyzed based on microsatellite markers. The resulting study showed evidence that provenance Muna has a Ho value 0f 0,65 or a relatively high genetic diversity value in comparison to provenance Bulukumba, Kolaka, and North Luwu.